2014
DOI: 10.1007/s00228-014-1666-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 fatty acids on depressive symptoms and inflammatory markers in maintenance hemodialysis patients: a randomized, placebo-controlled clinical trial

Abstract: Supplemental use of omega-3 fatty acids decreases depressive symptoms in hemodialysis patients apart from their anti-inflammatory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 49 publications
0
77
1
2
Order By: Relevance
“…During the initial electronic search, 285 manuscripts were identified, of which 243 were excluded including duplicates, study with other design, and unrelated studies. The full text of 42 manuscripts was retrieved, and after detailed evaluation, 23 RCTs including 20 datasets were finally selected for meta-analysis1112131415161718192021222324252627282930313233. No new eligible studies were identified in manual search.…”
Section: Resultsmentioning
confidence: 99%
“…During the initial electronic search, 285 manuscripts were identified, of which 243 were excluded including duplicates, study with other design, and unrelated studies. The full text of 42 manuscripts was retrieved, and after detailed evaluation, 23 RCTs including 20 datasets were finally selected for meta-analysis1112131415161718192021222324252627282930313233. No new eligible studies were identified in manual search.…”
Section: Resultsmentioning
confidence: 99%
“…CRP levels were unchanged in patients with stage 4e5 CKD, who were given 1.8 g or 3.6 g of n-3 fatty acids daily for 10 weeks [33], and in hemodialysis patients that received 3 g/day of n-3 fatty acids for 2 months [34]. In contrast, a significant reduction in CRP was observed in hemodialysis patients after 4 months supplementation with n-3 fatty acids (900 mg/day) [35], and in patients with end-stage renal disease who were given 1.56 g/day of n-3 fatty acids for 6 months [36]. It has been suggested that n-3 fatty acids are more effective when CRP is elevated at baseline and this may in part have contributed to the different study outcomes [37,38].…”
Section: Discussionmentioning
confidence: 95%
“…36 Another RCT in HD patients showed that 4 months supplementation with omega-3 fatty acids not only decreased depressive symptoms but also reduced inflammatory status; however, results were considered as inconclusive. 37 Finally, as cognitive behavioral therapy not only corrected disorganized sleep patterns but also reduced inflammation and oxidative stress in HD patients, 38 this further support links between psychosocial health and inflammation.…”
Section: General Lifestyle Modifications That May Have Anti-inflammatmentioning
confidence: 92%